The Role of Craft Breweries in Expanding (Local) Hop Production. (November 2019) - Dobis, Elizabeth A.; Reid, Neil; Schmidt, Claudia; Goetz, Stephan J.
Abstract: Hop production has expanded dramatically in recent years along with the number of local craft breweries, but to date the relationship between these two phenomena has not been explored systematically. Using a state-level pooled count data model with observations from 2007, 2012, and 2017, we examine the independent lagged effects of breweries on the number of hop farms and acres grown, holding constant fixed effects and key economic and geographic factors. Our results confirm that the number of breweries is associated with more hop production (farms and acres) five years later, while warmer temperatures and higher land prices discourage it. (JEL Classifications: L66, Q11, R30)